Short Communication: Density and length-weight relationship of mudskipper (Periophthalmus spp.) in the mangrove area of Kairatu Beach, Maluku, Indonesia - Diana Taniwel; Fredy Leiwakabessy; Dominggus - Rumahlatu (Society for Indonesian Biodiversity, 2020)
Abstract. Taniwel D, Leiwakabessy F, Rumahlatu D. 2020. Short Communication: Density and length-weight relationship of mudskipper (Periophthalmus spp.) in the mangrove area of Kairatu Beach, Maluku, Indonesia. Biodiversitas 21: 5465-5473. Mudskippers (genus Periophthalmus) fish species inhabit mudflat, sandy beaches, and mangrove areas. Their daily activities are influenced by tidal rhythms. The aim of this research was to identify the species of mudskipper, their density, and length-weight relationship of more density species in the mangrove area of ??Kairatu beach, Maluku, Indonesia. This research was conducted from July to August 2018, 3 sampling sites using purposive sampling technique. The physical-chemical parameters of environmental conditions (temperature, dissolved oxygen, salinity, and pH of water) were measured directly on location (in-situ), while the different mudskippers species present in the study sites were identified in the laboratory at the Pattimura University. Quantitative data on population density and length and weight of individuals were obtained for four Periophthalmus species. The physical-chemical parameters of environmental conditions in the three sampling stations were within the range of optimal values previously obtained for mudskipper species. The temperatures ranged from 30.01-30.05 oC, the dissolved oxygen ranged from 7.1-7.5 mg/L, the pH ranged from 7.3-7.5, and the salinity ranged from 5-7 ‰. The four mudskippers species identified in the sampling sites were (in density descending order): Periophthalmus argentilineatus (5.05 ind/m2), P. gracilis (1.5 ind/m2), P. malaccensis (0.4 ind/m2) and P. kalolo (0.3 ind/m2). The results of the regression analysis showed that there was no significant relationship between physical-chemical parameters to mudskipper density. The results of the length-weight relationship of the two most abundant species P. argentilineatus and P. gracilis a negative allometric length-weight relationship (b<3), while the P. kalolo and P. malaccensis indicated a positive allometric growth type (b>3).